2015
DOI: 10.1097/htr.0000000000000036
|View full text |Cite
|
Sign up to set email alerts
|

Differential Eye Movements in Mild Traumatic Brain Injury Versus Normal Controls

Abstract: A reliable, standardized protocol that appears to differentiate mTBI from normals was developed for use in future research. This investigation represents a step toward objective identification of those with PCS. Future studies focused on increasing the specificity of eye movement differences in those with PCS are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
105
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 21 publications
7
105
5
Order By: Relevance
“…They corroborate findings from sports concussion cohorts showing mTBI with PTA has a poorer prognosis than mTBI without PTA [42]. As one would expect given the high incidence of visual tracking deficits seen with mTBI [43], the CPT conditions targeting inaccurate visual feedback (condition 3) or deprived visual and proprioceptive feedback (condition 5) were particularly sensitive to mTBI with PTA. On the contrary, when normal visual inputs were available as in conditions 1 and 4, regardless of the presence of normal or altered proprioceptive input (a sense infrequently affected by mTBI), there were no group differences.…”
Section: Conclusion No Blast Mtbi With Pta Versus Blast Mtbi With Ptasupporting
confidence: 82%
“…They corroborate findings from sports concussion cohorts showing mTBI with PTA has a poorer prognosis than mTBI without PTA [42]. As one would expect given the high incidence of visual tracking deficits seen with mTBI [43], the CPT conditions targeting inaccurate visual feedback (condition 3) or deprived visual and proprioceptive feedback (condition 5) were particularly sensitive to mTBI with PTA. On the contrary, when normal visual inputs were available as in conditions 1 and 4, regardless of the presence of normal or altered proprioceptive input (a sense infrequently affected by mTBI), there were no group differences.…”
Section: Conclusion No Blast Mtbi With Pta Versus Blast Mtbi With Ptasupporting
confidence: 82%
“…It is therefore becoming more common to integrate oculomotor assessments into evaluations of neurophysiological and neurodegenerative (Crawford et al, 2005) disorders and injury. Oculomotor assessments are especially useful for detecting deficits that occur as a consequence of brain injury; it has been established that closed head injury can result in significant impairments in oculomotor and visuomotor function (Cifu et al, 2015;Heitger et al, 2004;Suh, et al, 2006a, b). Specifically, these common oculomotor impairments include reductions in spatial accuracy of saccadic eye movements, increased lag during smooth pursuit tracking, reduced peak saccade velocities and accelerations (Cifu et al, 2015), and delays and errors in planning, decision-making and other executive functions (Heitger et al, 2002(Heitger et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The overall mean time since injury was 4.2 yr (SD = 4.9 yr). This compares to, for example, the study cohorts of Cifu et al [10], where the mean time since the most recent mTBI was 8.5 mo (SD = 6.58 mo) and Contreras et al [8] (2.2 yr ± 1.8 yr). One of the forward-looking results is the further enhancement of the sensitivity of the CBIAS through the modification and incorporation of other eye tests as well as the incorporation of neurocognitive tests into the CBIAS battery.…”
Section: Discussionmentioning
confidence: 49%
“…As noted by Contreras et al [13] and Cifu et al [10], two-dimensional SPEM tests demonstrated the highest effectiveness (AUC = 0.88). Furthermore, more challenging horizontal tests, such as the faster random sinusoidal assessment (AUC = 0.79), resolved differences better than less challenging assessments, specifically the simple sinusoidal as well as the slow random horizontal tests.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation